2018
DOI: 10.1177/0954410017749867
|View full text |Cite
|
Sign up to set email alerts
|

Dual combustor ramjet engine dynamics modeling and simulation for design analysis

Abstract: An integrated low-order, medium-fidelity model for a dual combustor ramjet engine configuration is derived for use in mission analysis and controller design. Each of the individual components – intake, isolator, ram diffuser and combustor, scram combustor and nozzle – are modeled using either empirical data or analytical relations, or in case of the two combustors by using a quasi-one-dimensional code. The components are appropriately linked to capture the key physical phenomena inherent in the dual combustor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…A novel model was developed by Wadwankar et al 14 to estimate the DCR engine performance under varying equivalence ratios. The combustion characteristics of the DCR engine are numerically investigated by Zang et al 15 The authors revealed that stable combustion could be observed at the nozzle rim, and the mixing layer regimes are formed by increasing the fuel equivalence ratios.…”
Section: Introductionmentioning
confidence: 99%
“…A novel model was developed by Wadwankar et al 14 to estimate the DCR engine performance under varying equivalence ratios. The combustion characteristics of the DCR engine are numerically investigated by Zang et al 15 The authors revealed that stable combustion could be observed at the nozzle rim, and the mixing layer regimes are formed by increasing the fuel equivalence ratios.…”
Section: Introductionmentioning
confidence: 99%